Dinamika Sosial Ekonomi Penambang Pasir Tradisional di Desa Mataraman (1960-2010) - Norhidayat Norhidayat; Rochgiyanti Rochgiyanti; Rusdi Effendi (Yupa: Historical Studies Journal, 2017)
This research oriented at the traditional mining sand in the village of Mataraman that is the business sector labor-intensive and has long lasting. The purpose of this research is to know about the lives of the miners traditional sand in the village of Mataraman sub-district Banjar Regency. The worst of conditions happened in the past years 1995 to 2000, while the best conditions during this time is the condition post monetary crisis over five years is 2000 and 2005. Sand mining in the village Mataraman also provides role for the economy villagers Mataraman, provide jobs, and becomes a magnet the economic activities and expand their villages indirectly also bring economic impact to its villagers